Parallels of epic formulas in the Yakut olonkho and Tuvan epic: a comparative aspect - Borisov, Yuri Petrovich (The New Research of Tuva, 2020)
The article aims to identify parallels and establish the cultural universals shared by the Yakut olonkho and the Tuvan epic at the level of epic formulas. The main methodology of the study was that of induction, which allows to summarize the outcomes of complete sampling, verification and description methods, as well as of component and contextual analysis. This study revealed the total of 82 epic formulas in the text of the Tuvan epic “Boktug Kirish, Bora Sheley” as told by storyteller M. N. Oorzhak, as well as parallels in 17 examples. 9 formulae were specifically analyzed in the article, with analogues found in the texts of the Yakut olonkho (several versions). The article treats these examples as ‘typical places’, universal in their intertextuality. At the same time, the structural features of the epic formulas reflect the stadial difference between the epic systems under comparison. The semantic load of epic formulae comes from their nuclear lexemes and peripheral elements, which are selected according to the principles of literal repetition and alliterative beginnings. Some examples, especially those organized with the use of a matrix construction, show the presence of full equivalents across key lexical items. The author concludes that considered parallels of the epic formulas have been determined by the genetic relationship between the Tuvan epic and the Yakut olonkho. These parallels have survived due to the general principle of rhythmic-syntactic parallelism.